Estigmatización territorial en acción - Wacquant, Loïc (2014)
This short article presents the thematic issue of the Environment & Planning A journal, which builds on the analytic framework elaborated by Wacquant in Urban Outcasts (2008) and on the activities of the Leverhulme Network on Advanced Urban Marginality to synthesize and stimulate inquiries into the triadic nexus of symbolic space, social space, and physical space at the lower end of the urban spectrum. The concept of territorial stigmatization weds Goffman's model of the management of "spoiled identity" with Bourdieu's theory of "symbolic power" to capture how the blemish of place impacts the residents of disparaged districts, the surrounding denizens and commercial operators, street-level public bureaucracies, specialists in cultural production (such as journalists, scholars, and politicians), and state officials and policies. Spatial taint is a novel and distinctive phenomenon that crystallized at century's end along with the dissolution of the neighborhoods of relegation emblematic of the Fordist-Keynesian phase of industrial capitalism. It differs from the traditional topography of disrepute in the industrial city in that it has become autonomized, nationalized and democratized, equated with social disintegration, racialized through selective accentuation, and it elicits revulsion often leading to punitive corrective measures. The sociosymbolic strategies fashioned by the residents of defamed quarters to cope with spatial denigration span a panoply ranging from submission to defiance, and their adoption depends on position and trajectory in social and physical space. Territorial stigmatization is not a static condition or a neutral process, but a consequential and injurious form of action through collective representation fastened on place. By probing how it operates in different urban settings and political formations, the contributors to the Environment and Planning A's issue advance our empirical understanding of the role of symbolic structures in the production of inequality and marginality in the city. They also suggest the need for public policies designed to reduce, not only the burden of material deprivation, but also the press of symbolic domination in the metropolis.